2022
DOI: 10.1007/s00404-022-06765-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of SARS-CoV-2 BNT162b2 vaccine on the symptoms of women with endometriosis

Abstract: Purpose As the use of the messenger RNA (mRNA) BNT162b2 (Pfizer-BioNTech) Coronavirus disease 2019 vaccine has grown, reports on menstrual changes have arisen. We aimed to examine menstrual bleeding patterns and endometriosis-associated symptoms after receiving the mRNA BNT162b2 SARS-CoV-2 vaccine in women with endometriosis, as compared to the control group. Methods This is a questionnaire-based cross-sectional study including a total of 174 women. The study group incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
(34 reference statements)
2
9
0
Order By: Relevance
“…This is consistent with our recent observation that adenomyosis is the most frequent conditions leading women of reproductive age to the emergency service for excessive bleeding [22]. Inconsistencies on bleeding side effects due to COVID-19 vaccine found in other studies may be the consequence of a not adequately evaluated presence of adenomyosis in the cohorts under investigations [15,16].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with our recent observation that adenomyosis is the most frequent conditions leading women of reproductive age to the emergency service for excessive bleeding [22]. Inconsistencies on bleeding side effects due to COVID-19 vaccine found in other studies may be the consequence of a not adequately evaluated presence of adenomyosis in the cohorts under investigations [15,16].…”
Section: Discussionsupporting
confidence: 91%
“…Manifestation of AUB or pain worsening differs from that observed in a 6 months follow-up period of non-vaccinated women with endometriosis or adenomyosis. The data indicate that about 16.8% of these women experience gynecological side effects, and add evidence to two recent studies performed in women with endometriosis [15,16].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, endometriosis was shown to be a significant risk factor for worsening of menstrual symptoms compared with the control group. 28 In the present study, up to 50% of the individuals included reported worsened or new menstrual-associated symptoms in the first cycle after vaccination, regardless of the presence of endometriosis. These alterations were reported to be transitory, because after the second cycle the rate decreased to ~30% in both groups.…”
Section: Discussionmentioning
confidence: 47%
“…In the previously published literature, Mattar reports a higher incidence of pelvic pain in an immunized cohort in comparison to a non-vaccinated cohort, but does not report the incidence in the same immunized cohort before immunization [ 15 ]. Another study from Israel has reported the worsening of dysmenorrhea in the cohort with and without endometriosis, but the information about positive improvement are is [ 16 ]. Additionally, another study has reported new incidence or worsening of dysmenorrhea by more than 47% of participants during the COVID-19 pandemic [ 17 ].…”
Section: Discussionmentioning
confidence: 99%